2019
DOI: 10.31248/jasp2019.161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of improved mung bean (Vigna radiata L.) varieties for yield in the moisture stress conditions of Abergelle Areas, Northern Ethiopia

Abstract: Mung bean (Vigna radiata L.) also known as green gram, golden gram, Oregon peas and chokoro (Swahili), is an economically important short duration legume crop for drought prone/ moisture stressed areas. Due to drought escape/early maturity in case of terminal drought in Ethiopia, improvement of grain yield of Mung bean (Vigna radiata L.) is the main objective to avoid food insecurity. A field experiment was carried out during the 2016 and 2017 main cropping seasons using a randomized complete block design with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Whereas interaction effect of year × treatment showed that days to 50% flowering, days to maturity, plant height, number of seeds/pod and test weight were only significant. Similar reports have been obtained from Belay et al (2019) stating that analysis of variance for six mung bean varieties exhibited differences in varietal characters viz. days to 50% flowering, plant height, number of seeds per pod, seed yield and thousand seed weight (p0.05) except number of pods per plant.…”
Section: Resultssupporting
confidence: 84%
“…Whereas interaction effect of year × treatment showed that days to 50% flowering, days to maturity, plant height, number of seeds/pod and test weight were only significant. Similar reports have been obtained from Belay et al (2019) stating that analysis of variance for six mung bean varieties exhibited differences in varietal characters viz. days to 50% flowering, plant height, number of seeds per pod, seed yield and thousand seed weight (p0.05) except number of pods per plant.…”
Section: Resultssupporting
confidence: 84%
“…Singh and Singh ( 2011) reiterated that susceptibility of mungbean to various abiotic stresses such as drought during various critical growth stages such as flowering and pod setting contributes mainly to yield loss. The differences in seed yield among the mungbean genotypes could be attributed to the inherent genetic potential of each genotype (Belay et al 2019). The complex processes involving the drought response in plants would play an important role in maintaining crop productivity under unfavorable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It's a warm-season annual pulse crop with a wide range of uses. The cowpea seeds are good source of protein for human, while the haulm is used as a source of protein for livestock (Belay et al, 2017) [6] . It is an important grain crop, particularly in arid and semi-arid regions of the tropics and sub-tropics.…”
Section: Introductionmentioning
confidence: 99%